IMPACT OF COVID-19 ON THE TOURISM INDUSTRY IN THE SIKKIM HIMALAYA - Bhutia, Sonam Tshering (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of the COVID-19 pandemic on the tourism industry in Sikkim, a region known for its natural beauty and cultural heritage. The analysis highlights the decline in tourist arrivals and revenue, resulting in economic challenges for local businesses and communities reliant on tourism. It also explores the adaptations made by stakeholders, including a shift toward domestic tourism, the implementation of safety measures, and the use of technology to enhance visitor experiences. Additionally, the study discusses future prospects for tourism in Sikkim, emphasizing opportunities for sustainable development and the importance of community engagement in recovery efforts. Key recommendations for stakeholders include collaboration on recovery strategies, investment in infrastructure, and a focus on wellness tourism. The findings suggest that, despite the challenges posed by the pandemic, Sikkim's tourism sector has the potential to rebuild and thrive through resilience and innovative practices.